Pengaruh Buku Pop-Up terhadap Penguasaan Kosakata Siswa - Susrianty, Nindy (ELP (Journal of English Language Pedagogy), 2024)
The research addressed the issue of insufficient vocabulary mastery among eighth-grade students at SMPN 1 Kubung during the 2022/2023 academic year. The students' limited proficiency in vocabulary was attributed to factors such as rote memorization and the lack of diverse instructional media. Consequently, pop-up books were selected as a teaching medium to investigate their impact on students' vocabulary mastery. The research employed a quasi-experimental design, and the population comprised 94 eighth-grade students at SMPN 1 Kubung for the 2022/2023 academic year. Cluster random sampling was utilized to select a sample of 63 students, with 31 assigned to the experimental group and 32 to the control group. The experimental and control groups were determined through a random draw. The pre-test score averaged 32.68, but it significantly increased to 70.41 after the intervention. Analysis using an independent samples T-test indicated that pop-up books had a more substantial impact compared to traditional pictures. The rejection of the null hypothesis (H0) suggested a significant positive effect of using pop-up books as a teaching medium on students' vocabulary mastery in the eighth grade at SMPN 1 Kubung for the 2022/2023 academic year. Based on the findings, it is recommended that teachers consider this research when exploring a broader range of teaching media to enhance student engagement in vocabulary learning. Furthermore, future researchers are encouraged to explore additional avenues for improvement and refinement based on the insights gained from this study.